FAKTOR-FAKTOR PENDUKUNG PENINGKATAN KINERJA KARYAWAN DINAS PERIKANAN DAN KELAUTAN PROVINSI GORONTALO - Ad Mahmudy Irdja (Universitas Muhammadiyah Gorontalo, 2013)
Potential of marine and fishery resources in Gorontalo Province is estimated have enough opportunity, therefore this sector is expected can be one of strategic economy activities to develop local economy. For realize the expectation, Fishery and Marine Service of Gorontalo Province as technically authority and has public service function, has been improving professional skill and performance of its officials in order to presents excellent public service. Pass through this research will be studied about officials performance of the institute above mentioned. This research is aimed to: (1) know influence of trainings, facilities and standard operational procedures to official’s performance of Fishery and Marine Service of Gorontalo Province, and (2) know what factor is most significant influence to official’s performance of that institute. The methods of analyses are: (1) descriptive analyses, was used to see description of expedient to improved officials performance; (2) multiple regression analyses, was used to know the influence of trainings, facilities and standard operational procedures to officials performance; (3) t–test was used to know what factor is most significant influence to officials performance; and (4) other statistical test to completed. Finally, it was concluded that trainings, facilities and standard operational procedures significant influence simultaneity to official’s performance of Fishery and Marine Service of Gorontalo Province. Besides, among that three factors, the standard operational procedures is most influence individually to official’s performance. Therefore, Fishery and Marine Service of Gorontalo Province is suggested to improve trainings, facilities and standard operational procedures continuity in order to increasing official’s performance, especially the standard operational procedures as priority factor.